Microvascular significance of TGF-β axis activation in COVID-19 - Arguinchona, Lauren M.; Zagona-Prizio, Caterina; Joyce, Megan E.; Chan, Edward D.; Maloney, James P. (Frontiers in Cardiovascular Medicine, 2023)
As 2023 approaches, the COVID-19 pandemic has killed millions. While vaccines have been a crucial intervention, only a few effective medications exist for prevention and treatment of COVID-19 in breakthrough cases or in unvaccinated or immunocompromised patients. SARS-CoV-2 displays early and unusual features of micro-thrombosis and immune dysregulation that target endothelial beds of the lungs, skin, and other organs. Notably, anticoagulation improves outcomes in some COVID-19 patients. The protein transforming growth factor-beta (TGF-β1) has constitutive roles in maintaining a healthy microvasculature through its roles in regulating inflammation, clotting, and wound healing. However, after infection (including viral infection) TGF-β1 activation may augment coagulation, cause immune dysregulation, and direct a path toward tissue fibrosis. Dysregulation of TGF-β signaling in immune cells and its localization in areas of microvascular injury are now well-described in COVID-19, and such events may contribute to the acute respiratory distress syndrome and skin micro-thrombosis outcomes frequently seen in severe COVID-19. The high concentration of TGF-β in platelets and in other cells within microvascular thrombi, its ability to activate the clotting cascade and dysregulate immune pathways, and its pro-fibrotic properties all contribute to a unique milieu in the COVID-19 microvasculature. This unique environment allows for propagation of microvascular clotting and immune dysregulation. In this review we summarize the physiological functions of TGF-β and detail the evidence for its effects on the microvasculature in COVID-19. In addition, we explore the potential role of existing TGF-β inhibitors for the prevention and treatment of COVID-19 associated microvascular thrombosis and immune dysregulation.